2020
DOI: 10.1186/s13229-020-00390-x
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of laminar-specific excitatory and inhibitory circuits of the orbitofrontal cortex in autism

Abstract: Background The human orbitofrontal cortex (OFC) is involved in assessing the emotional significance of events and stimuli, emotion-based learning, allocation of attentional resources, and social cognition. Little is known about the structure, connectivity and excitatory/inhibitory circuit interactions underlying these diverse functions in human OFC, as well as how the circuit is disrupted in individuals with autism spectrum disorder (ASD). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 99 publications
1
13
0
Order By: Relevance
“…Anatomical studies of OFC in ASD (reviewed in Rolls & Grabenhorst, 2008) have revealed abnormalities its size and structure, and more recently, Liu et al (Liu et al, 2020) have reported post-mortem histological abnormalities in the right OFC of adult ASD individuals, with laminar-specific abnormalities of inhibitory neurons distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical studies of OFC in ASD (reviewed in Rolls & Grabenhorst, 2008) have revealed abnormalities its size and structure, and more recently, Liu et al (Liu et al, 2020) have reported post-mortem histological abnormalities in the right OFC of adult ASD individuals, with laminar-specific abnormalities of inhibitory neurons distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Anatomical studies of the orbitofrontal cortex (OFC) in ASD (reviewed in Liu et al, 2020) have revealed abnormalities in the size and the structure of the OFC, together with differences in the subcortical white matter (WM) in this region, and more recently, Liu et al (2020) have reported post-mortem histological abnormalities in the right OFC of adult ASD individuals, with laminarspecific abnormalities of the density and the diameter of myelinated axons in that specific area.…”
Section: Introductionmentioning
confidence: 99%
“…Increased neuron numbers within the PFCx are noted in children with ASD [17]. Moreover, disturbed cortical excitation-inhibition balance is considered to be one of the pathophysiological mechanisms of ASD [60][61][62]. TAOK2 belongs to the MAP kinase kinase kinase (MAP3K) family, which regulates the p38 MAPK, SAPK/JNK and Hippo signaling pathways [63].…”
Section: Discussionmentioning
confidence: 99%
“…ASD is commonly characterized by functional deficits in social behavior, difficulties in social communication, and restricted and repetitive interests (American Psychiatric Association, 2013). Such social impairment is a defining phenotypic feature of ASD (Ogawa et al, 2019;Liu et al, 2020). Previous studies of individuals with ASD have found diminished motivation to engage in social activities (Tsurugizawa et al, 2020), deficits in reciprocal social communication (De Crescenzo et al, 2019), and deficits in the ability to understand the beliefs and intentions of others (Chevallier et al, 2012;Ruta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%